The development of corporate legitimacy measurement forgovernment-linked companies in Malaysia / Mahadir Ladisma @ Awis, Hazman Shah Vijayan Abdullah and Norziana Lokman - Ladisma @ Awis, Mahadir; Abdullah, Hazman Shah Vijayan; Lokman, Norziana (Universiti Teknologi MARA, Shah Alam, 2017)
The aim of this paper is to develop the measurement of corporate legitimacy among Government-linked Companies (GLCs) in Malaysia. Corporate legitimacy is important for determining the survival of the corporation. The term of legitimacy can be classified into three different aspects, namely; political, economic and social legitimacy. Political legitimacy indicates the right of govern and rule; economic legitimacy reflects on success through product selling, customers' satisfaction and providing better services and goods. However, in the corporate sectors, corporate social responsibility is used as a platform not only to gain economic legitimacy, but most importantly to achieve social legitimacy. Social legitimacy focuses on corporation as a societal institution that is more complex by combining the social norms, values and expectation. With the above argument, this paper explores how corporate social responsibility (or corporate responsibility) can be used to show societal acceptance reflecting their corporate legitimacy. The corporations are expected to be socially acceptable; according to social norms, values and beliefs. The growth of the corporation has faced a number of challenges in gaining and maintaining their existence. While the corporations are expected to deal with the challenges effectively, the corporation must also be relevant in the eyes of the stakeholders. To establish this, corporation emphasized on gaining and maintaining legitimacy through various mechanisms. The principles of legitimacy are related to the conformity to the norms, values and expectation of their stakeholders' engagement through corporate social activities. The study employed a cross-sectional sample survey designed to collect data from a pre-selected list of non-governmental organization (NGOs) obtained from the Registrar of Societies, Malaysia. From a list of about 22,000 societies, 377 were shortlisted covering five categories of societies; community welfare, education, sport, social and recreation, business and trade union. This study measured three dimensions of corporate legitimacy comprising pragmatic, moral and cognitive legitimacy. Using Partial Least Square-Structural Equation Modeling (PLS-SEM), this study found that there is high level of corporate legitimacy from the perspective of NGOs, which indicated that the NGOs highly view the corporate legitimacy of Malaysian GLCs through their corporate responsibility activities.